Influence of the geometry aspect of jars on the heat transfer and flow pattern during sterilization of liquid foods - Lespinard, Alejandro Rafael (2012)
Natural convection heating of liquid food packed in glass jars of different sizes and volumes during sterilization is simulated by solving the governing equations for continuity, momentum and energy conservation, using the finite element method. The effect of the aspect ratio of the container on temperature distribution, flow pattern, position of the slowest heating zone (SHZ) and cooking value were analyzed. The position of the SHZ varied – depending of container volume and aspect ratio – in the range of 49.39–76.83% and 5.81–19.09% of jar radius and height, respectively. Sterilization times were estimated and differences between 135 and 105 s for containers of a same size of 360 or 660 cm3, respectively, were predicted depending on jar shape. A prediction model was developed that allows to calculate – with a simple procedure – sterilization times as a function of container dimensions.